2006
DOI: 10.1248/bpb.29.234
|View full text |Cite
|
Sign up to set email alerts
|

Role of Polyamines Derived from Arginine in Differentiation and Proliferation of Human Blood Cells

Abstract: The murine cationic amino acid transporter 1 (mCAT1) protein mediates membrane transports of L-arginine, L-lysine, L-histidine, and L-ornithine. The importance of mCAT1-mediated transport was underscored by the phenotype of mCAT1 gene-knockout mice, which exhibit anemia. 1) In addition, we reported that L-arginine that is a substrate of CAT1 is essential for the differentiation to erythrocyte by in vitro cell culture study.2) It has been also observed that L-arginine deficiency affects maturation of early B ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
44
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 24 publications
6
44
0
Order By: Relevance
“…Since changes in arginine-derived metabolites, such as nitric oxide and polyamines, are known to influence erythroid differentiation [7,8,[16][17][18]21], modifications of intracellular arginine availability may alter the metabolism of the cationic amino acid and hence have physiological relevance. In this context, if CAT1-mediated arginine influx is needed for erythroid differentiation [23,29], the y + LAT2-mediated efflux of the amino acid may behave as a brake, avoiding excessive increase in the intracellular arginine concentration and inappropriate activation of metabolic pathways during the differentiation process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since changes in arginine-derived metabolites, such as nitric oxide and polyamines, are known to influence erythroid differentiation [7,8,[16][17][18]21], modifications of intracellular arginine availability may alter the metabolism of the cationic amino acid and hence have physiological relevance. In this context, if CAT1-mediated arginine influx is needed for erythroid differentiation [23,29], the y + LAT2-mediated efflux of the amino acid may behave as a brake, avoiding excessive increase in the intracellular arginine concentration and inappropriate activation of metabolic pathways during the differentiation process.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the differentiation of erythroid precursors requires polyamines [21] and arginase; this enzyme catalyzes the first step in polyamine biosynthesis and is induced during the differentiation of K562 cells promoted by sodium phenylbutyrate [18]. Hence, it is not surprising that the availability of extracellular arginine, the precursor of both nitric oxide and polyamines, influences the expression of globin genes [16].…”
Section: Introductionmentioning
confidence: 99%
“…Polyamines were also shown to regulate cell differentiation in several cell types (Fernandez-Pinilla and Pestana 1987;Gavin et al 2004;Pietila et al 2005;Maeda et al 2006). The encystment-specific vesicles (ESV) and clefts Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that OCTN1 was strongly expressed in glycophorin A-positive erythroid cells and was associated with erythroid-lineage cells at the transition stage from immature erythroid cells to peripheral mature erythrocytes (7). In addition, the small molecules that are transported by transporters such as, L -arginine, polyamine, and thiamine are associated with cell differentiation (15,25,26). Accordingly, it is considered that OCTN1 physiologically transports small molecule(s) that are essential for normal cell growth and differentiation to erythrocytes.…”
Section: Discussionmentioning
confidence: 99%